Microbial contamination in the ethanol and cachaça fermentation process: impacts and applications - OLIVEIRA, Amanda Cristina Dias de; OLIVEIRA, Carlos Augusto Fernandes de; KAMIMURA, Eliana Setsuko (Food Science and Technology, 2023)
Brazil is a major powerhouse in the production of sugarcane. Consequently, several supply chains use it as a raw material, such as the food sector, mainly in the production of sugar and beverages, such as cachaça, and the biofuels sector, with the production of ethanol, an important product for the Brazilian economy. The production of cachaça and ethanol share an important stage known as fermentation, a fundamental process that defines the quality and yield of the alcoholic fermentation product, which is achieved using Saccharomyces cerevisiae. Different industrial strains have been selected to promote alcoholic fermentation efficiently and with high productivity. However, it is possible that microorganisms from various stages of the production chain reach the fermentation phase, compromising it. Contaminants can vary from different genera of yeasts, including Dekkera and Pichia, to bacteria, mainly belonging to the Lactobacillaceae family, which produce lactic acid. Contaminating microorganisms affect the fermentation stage and, as a consequence, the quality of the produced cachaça or the production efficiency of ethanol. Recent studies have shown that these contaminants, in addition to resulting in negative aspects of sugarcane fermentation, can also present interesting physiological characteristics that can be applied in bioprocesses in other productive sectors or to improve fermentation strains.